Implementation of Leadership Style Toward Quality Papua Human Resources : (Study at the Semarang Binterbusih Foundation) - Beanal, Yance; Rumijati, Aniek; Mursidi, Mursidi (University of Muhammadiyah Malang, 2022)
This research focuses on exploring the themes and meanings from the informants' knowledge as deeply as possible through interpretative phenomenological analysis, resulting in a detailed description. The qualitative research approach used is the phenomenological approach of Alfred Schutz, which helps understand and uncover the meaning behind various visible phenomena from detailed descriptions. The data collection methods used are observation, interviews, and documentation. Data analysis techniques are used to check the validity of the data, analyze the identification of themes and meanings, and form propositions and research findings. The results of the analysis are as follows: 1) understanding the meaning of coaching, leadership, intellect and spirituality in achievement is conveyed by the statement of Informant I as the manager of the Bunterbusih Program, Informant II by the chairman of the Bunterbusih Foundation, and Informant III as coaching, and 2) Leadership style implemented in agencies the Binterbusih Foundation institution consists of a Directive, Supportive, Participative, and achievement-oriented leadership style simultaneously or together towards quality Papuan human resources (studies at the Binterbusih Semarang foundation). In other words, if the directive, supportive, participatory, and achievement-oriented leadership style improves, it can increase the quality of Papuan human resources.